Entrepreneurial Risk-Taking: Implications From Risk-Sensitivity Theory (American Journal of Management, 2021)
Entrepreneurship is a risky endeavor. Why do some people decide to accept entrepreneurial risks in order to obtain possible financial and non-financial returns? The debate over this question has been going on for decades, but it has never ended. In this study, I join the debate and attempt to answer the question based on risk-sensitivity theory. The main idea behind the theory is that need motivates risk-taking behaviors. I review the literature on entrepreneurial risk-taking and focus on four broad approaches: trait, demographic, environmental, and cognitive. I develop an integrative framework based on risk-sensitivity theory. The framework recognizes the value of different approaches to entrepreneurial risk-taking. At the same time, it also addresses the limitations of each approach if used alone. My central argument is that people take entrepreneurial risks because other less risky options cannot meet their needs.
Keywords: management; entrepreneurship; risk-taking; risk-sensitivity theory; need